2018
DOI: 10.18520/cs/v115/i12/2249-2258
|View full text |Cite
|
Sign up to set email alerts
|

Evapotranspiration and Crop Coefficient of Okra under Subsurface Drip with and without Plastic Mulch

Abstract: Field experiments using lysimeters were conducted in sub-humid climatic condition to estimate water balance parameters, regional crop coefficient development and to evaluate yield response of okra crop under subsurface drip (SSD) irrigation with and without plastic mulch. In the year 2016, total crop evapotranspiration under SSD with and without plastic mulch was 403 and 512 mm respectively, whereas in 2017 it was 363 and 468 mm respectively. Average crop coefficient of okra was 0.31, 0.42, 0.68, 0.77 and 0.48… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 12 publications
(18 reference statements)
0
3
0
Order By: Relevance
“…Mulching has become an important practice in modern field production due to benefits such as increase in soil temperature [7,8] reduced weed pressure [9] moisture conservation [10], water saving and increase water use efficiency [11], reduction of certain insect pests [12] reducer soil erosion [13], higher crop yields [14] and more efficient use of soil nutrients. The stem diameter, plant height, internodes length, number of fruits/plant, weight of fruits/plant and fruit yield were recorded as 13.60 mm, 123.54 cm, 12.83 cm, 20.80, 216.68 gm and 10318.13 kg/ha respectively in silver black plastic mulch while it was found minimum in no mulch which was matched with [15,16,17]. Similar results were also obtained by [18] in chili and [19] in brinjal cultivation.…”
Section: Effect Of Mulch On Yield and Yield Attributementioning
confidence: 62%
“…Mulching has become an important practice in modern field production due to benefits such as increase in soil temperature [7,8] reduced weed pressure [9] moisture conservation [10], water saving and increase water use efficiency [11], reduction of certain insect pests [12] reducer soil erosion [13], higher crop yields [14] and more efficient use of soil nutrients. The stem diameter, plant height, internodes length, number of fruits/plant, weight of fruits/plant and fruit yield were recorded as 13.60 mm, 123.54 cm, 12.83 cm, 20.80, 216.68 gm and 10318.13 kg/ha respectively in silver black plastic mulch while it was found minimum in no mulch which was matched with [15,16,17]. Similar results were also obtained by [18] in chili and [19] in brinjal cultivation.…”
Section: Effect Of Mulch On Yield and Yield Attributementioning
confidence: 62%
“…Plastic film mulching is a vital field management technology for agricultural production, improving crop yields while minimizing water input 4‐6 . The drip irrigation technology under mulching, which combines drip irrigation with plastic film mulching, can improve the soil temperature, reduces evaporation between plants, reduces deep leakage, and allows the application of water to be balanced against the yield 7‐9 . For example, Sui et al .…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6] The drip irrigation technology under mulching, which combines drip irrigation with plastic film mulching, can improve the soil temperature, reduces evaporation between plants, reduces deep leakage, and allows the application of water to be balanced against the yield. [7][8][9] For example, Sui et al reported that drip irrigation under mulching significantly increases yield by 10-29% and water use efficiency by 10-31% with nitrogen (N) of 230 kg hm −2 . 10 Zong et al demonstrated that drip irrigation under film increased the soil moisture and temperature, especially during the early and middle growth stages of cotton.…”
Section: Introductionmentioning
confidence: 99%